CMT type 2N disease-associated AARS mutant inhibits neurite growth that can be reversed by valproic acid. (February 2019) - Tatsumi, Yuriko; Matsumoto, Naoto; Iibe, Noriko; Watanabe, Natsumi; Torii, Tomohiro; Sango, Kazunori; Homma, Keiichi; Miyamoto, Yuki; Sakagami, Hiroyuki; Yamauchi, Junji
Highlights: Wild type AARS is localized in the cytoplasmic region. The CMT2 N-associated AARS mutant is localized throughout the organelles. The mutant inhibits differentiation in N1E-115 cells. Valproic acid reverses the effect of the CMT2 N-associated AARS mutant. Abstract: Charcot-Marie-Tooth (CMT) disease is composed of a heterogeneous group of hereditary peripheral neuropathies. The peripheral nervous system primarily comprises two types of cells: neuronal cells and myelinating glial Schwann cells. CMT2 N is an autosomal dominant disease and its responsible gene encodes alanyl-tRNA synthetase (AARS), which is a family of cytoplasmic aminoacyl-tRNA synthetases. CMT2 N is associated with the mutation, including a missense mutation, which is known to decrease the enzymatic activity of AARS, but whether and how its mutation affects AARS localization and neuronal process formation remains to be understood. First, we show that the AARS mutant harboring Asn71-to-Tyr (N71Y) is not localized in cytoplasm. The expression of AARS mutant proteins in COS-7 cells mainly leads to localization into lysosome, whereas the wild type is indeed localized in cytoplasm. Second, in N1E-115 cells as the neuronal cell model, cells expressing the N71Y mutant do not have the ability to grow processes. Third, pretreatment with antiepileptic valproic acid reverses the inhibitory effect of the N71Y mutant on process growth. Taken together, the N71Y mutation of AARS leads to abnormal intracellular localization, inhibiting process growth, yet this inhibition is reversed by valproic acid.